Cinacalcet exhibits rapid bactericidal and efficient anti-biofilm activities against multidrug-resistant Gram-positive pathogens - Yanpeng Xiong; Shanghong Liu; Jinxin Zheng; Jinlian Chen; Zewen Wen; Xiangbin Deng; Bing Bai; Duoyun Li; Zhijian Yu; Shiqing Han; Xiaoju Liu; Peiyu Li (iScience, 2023)
Summary: Infections caused by Gram-positive bacteria pose a serious threat to global public health. Drug resistance, dormant persister cells, and biofilm formation are the key challenges affecting the efficacy of antibiotics against Gram-positive bacterial infections. In this study, cinacalcet exhibited good inhibitory activity against multidrug-resistant Gram-positive bacteria, with minimum inhibitory concentrations (MICs) ranging from 3.13 μg/mL to 25 μg/mL. Cinacalcet displayed more rapid and stronger bactericidal activity against planktonic and persister cells of Staphylococcus aureus and Enterococcus faecalis compared with the antibiotics vancomycin or ampicillin, as well as potent inhibition and eradication of mature biofilms of methicillin-resistant S. aureus (MRSA) and linezolid-resistant E. faecalis (LRE). In addition, the robust antibacterial activity was demonstrated in vivo by a pneumonia infection model and a biofilm formation and deep-seated infection model. Collectively, these findings indicate that cinacalcet may be a promising new candidate antibiotic to combat infections caused by multidrug-resistant Gram-positive pathogens.